Corporate Governance, Board Diversity dan Underpricing Perusahaan Initial Public Offering (IPO) yang Terdaftar di Bursa Efek Indonesia Tahun 2010-2024 - Sutrisno Sutrisno; Dimas Nova Dhiansyah (Jurnal Pendidikan Indonesia, 2025)
The phenomenon of underpricing of shares in the Initial Public Offering (IPO) has become a critical issue in the Indonesian capital market, where the stock price on the first day of trading often far exceeds the initial offering price. This condition causes potential losses for issuers and indicates market inefficiency. The main objective of this study is to examine the effect of Corporate Governance, Board Diversity, and Underpricing on Initial Public Offering (IPO) companies listed on the Indonesia Stock Exchange for the period 2010–2024. A panel data regression model is used to determine the effect of these variables. The sample consists of companies conducting IPOs on the Indonesia Stock Exchange during the 2010–2024 period. The independent variables considered include Board Diversity (specifically Female Board Members (FB) and Board Member Age (AA)), Board Size (BS), Board Committee (BC), Board Independence (BI), Related Board Members (RBM), Board Member Position (BP), and Top Ten Shareholders (Top 10). Underpricing (UP) serves as the dependent variable. The analysis results indicate that female board members have a negative effect on underpricing, and Top Ten Shareholding also has a negative effect on underpricing.